Identifikasi Jenis-Jenis Tumbuhan Lumut (Bryophyta) Di Kawasan Wisata Air Terjun Takapala Malino - Syamsiah, . (bionature, 2009)
Identification of Bryophytes (Mosses) plant species have been done. This research was based on morphological characters of mosses at tour location Takapala Waterfal in Malino. The result shows that there are twelve species of Bryophytes, from two classis (Hepaticae and Musci). Hepaticae classis consist of three species, and Musci classis consist of nine species. Â  Keywords: identification, bryophytes